Deciphering Global STEM Attitudes through Insightful Correlations for Education: Menguraikan Sikap STEM Global melalui Korelasi yang Berwawasan untuk Pendidikan - Ummah, Munfiathul; Shofiyah, Noly (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores students' attitudes towards STEM and the relationship between STEM dimensions in Muhammadiyah Sidoarjo Junior High School, which implements STEM-based science learning. Through a survey of 85 students, it was found that students' attitudes were most dominant in the integrated STEM dimension and lowest in mathematics. However, the correlation between STEM dimensions varied, with technology and engineering showing no correlation with mathematics. These findings suggest that educators can leverage students' positive attitudes towards integrated STEM activities to improve engagement and learning outcomes. Furthermore, understanding the lack of correlation between certain STEM dimensions can inform curriculum adjustments for more effective integration of these disciplines in junior high school education. Hightligh: Strong preference for integrated STEM. Varied correlation between STEM dimensions. Informs curriculum adjustments for effective integration. Keywords: STEM education, attitudes, Muhammadiyah Sidoarjo Junior High School, correlation, curriculum development